1999
DOI: 10.1007/s002619900495
|View full text |Cite
|
Sign up to set email alerts
|

Impact of double helical CT and three-dimensional CT arteriography on surgical planning for hepatic transplantation

Abstract: DHCT/3D-CTA provides noninvasive means to identify findings that have significant impact on surgical planning for hepatic transplantation including celiac axis stenosis, diameter of inflow arterial vessel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 15 publications
1
30
1
2
Order By: Relevance
“…Not all arteries are visualised due to their anatomic position, including CA, SMA and IMA [25,59]. Computerised topographic angiography and magnetic resonance angiography are precise, objective and repeatable [66,99] but method they apply (3-dimensional reconstruction of vessels filled with contrast material) is probably superior for lumen rather than diameter estimation. Also they are usually performed at diseased populations, are relative expensive and not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…Not all arteries are visualised due to their anatomic position, including CA, SMA and IMA [25,59]. Computerised topographic angiography and magnetic resonance angiography are precise, objective and repeatable [66,99] but method they apply (3-dimensional reconstruction of vessels filled with contrast material) is probably superior for lumen rather than diameter estimation. Also they are usually performed at diseased populations, are relative expensive and not widely available.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also similar to those of Kopka et al (19), who correlated MRA with digital subtraction angiography in 60 patients and found that small accessory arteries were missed at MRA in 3/60 patients. Small-caliber aberrant hepatic arteries are generally ligated at transplantation surgery, and their presence usually does not impact the preoperative planning for arterial anastomosis performed at transplant surgery (4).…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative imaging plays a key role in evaluating factors that contraindicate or potentially expedite surgical transplantation (2)(3)(4). Multiphasic helical CT has proven useful in achieving these comprehensive goals (4 -10).…”
mentioning
confidence: 99%
“…Keywords: Celiac trunk variation; Axial tomography; Angiography reconstruction; Anatomical variation Knowledge of CeT variations is clinically relevant, specifically to determine the blood flow to specific organs [5]. It can help in the diagnosis of specific diseases, assist in selection of treatment options and surgical planning, facilitate surgical dissection, and help avoid iatrogenic injuries [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…It can help in the diagnosis of specific diseases, assist in selection of treatment options and surgical planning, facilitate surgical dissection, and help avoid iatrogenic injuries [3,5]. Advances in spiral and multidetector computed tomography technology has replaced invasive procedures for the study of this vessels [6,7].…”
Section: Introductionmentioning
confidence: 99%